PHỔ DẠNG SỐNG CỦA HỆ THỰC VẬT VƯỜN QUỐC GIA BA VÌ - Chấn, Lê Trần; Ninh, Trần Ngọc; Nhung, Huỳnh; Tứ, Nguyễn Hữu; Phượng, Đào Thị; Vân, Trần Thúy (Vietnam Journal of Earth Sciences, 2017)
There are five groups in the life-form spectra of the flora of Ba Vi National park : Phanerophytes -543 species (50,55 %), Chamephytes - 115 species (9,80 %), Hemicryptophytes - 295 species (25,14 %), Cryptophytes- 87 species (7,41 %) and Therophytes-83 species (7,12 %). The superiority of Phanerophytes is a common character of the humid tropical zone’s flora